The role of the distal elongation zone in the response of maize roots to auxin and gravity. - Ishikawa, H (1993)
We used a video digitizer system to (a) measure changes in the pattern of longitudinal surface extension in primary roots of maize (Zea mays L.) upon application and withdrawal of auxin and (b) compare these patterns during gravitropism in control roots and roots pretreated with auxin. Special attention was paid to the distal elongation zone (DEZ), arbitrarily defined as the region between the meristem and the point within the elongation zone at which the rate of elongation reaches 0.3 of the peak rate. For roots in aqueous solution, the basal limit of the DEZ is about 2.5 mm behind the tip of the root cap. Auxin suppressed elongation throughout the elongation zone, but, after 1 to 3 h, elongation resumed, primarily as a result of induction of rapid elongation in the DEZ. Withdrawal of auxin during the period of strong inhibition resulted in exceptionally rapid elongation attributable to the initiation of rapid elongation in the DEZ plus recovery in the main elongation zone. Gravistimulation of auxin-inhibited roots induced rapid elongation in the DEZ along the top of the root. This resulted in rapid gravitropism even though the elongation rate of the root was zero before gravistimulation. The results indicate that cells of the DEZ differ from cells in the bulk of the elongation zone with respect to auxin sensitivity and that DEZ cells play an important role in gravitropism.